2014
DOI: 10.1111/are.12542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on osmoregulation during the embryonic development of the bullseye puffer (Sphoeroides annulatusJenyns 1842)

Abstract: To evaluate the effect of salinity on the hatching rate, hatching time, survival percentage, osmoregulation pattern and the incidence of abnormalities in newly hatched larvae, embryos of Sphoeroides annulatus (Jenyns 1842) were exposed to 5, 12, 19, 26, 33, 35 and 40 psu. The hatching percentage (HP), survival percentage (PS), normal larvae (PN), deformed larvae (PD) and hatching time (HT) were significantly affected by salinity (P < 0.05). The embryos exposure to 5 psu caused that HP, PS, and PN had lower val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In this study, there was a trend of the incubation time to be inversely proportional to the increase in water salinity, fact observed in other marine fish species (Pérez‐Robles et al, 2014). Changes in the egg incubation time can affect the body size, the amount of yolk sac and oil drop reserves of newly hatched larvae of some fish (Gracia‐López et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…In this study, there was a trend of the incubation time to be inversely proportional to the increase in water salinity, fact observed in other marine fish species (Pérez‐Robles et al, 2014). Changes in the egg incubation time can affect the body size, the amount of yolk sac and oil drop reserves of newly hatched larvae of some fish (Gracia‐López et al, 2004).…”
Section: Discussionsupporting
confidence: 78%
“…It seems evident that there is no general rule applying to the growth response of fishes to salinity. Besides being species-specific, other biotic factors, such as age, body length and mass, as well abiotic factors, such as temperature and ionic composition of culture water, have been shown to interact with salinity to determine growth of fishes (Imsland et al, 2001;Sampaio & Bianchini, 2002;Wuenschel et al, 2004;Fielder et al, 2005;Varsamos et al, 2005;Pérez-Robles et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To understand S. annulatus salinity adaptation, Perez‐Robles et al () studied different developmental stages (eggs/embryos, larvae and juveniles) and exposure conditions (Table ). A difference for larva or juvenile was observed when trials were done by direct exposure or by acclimation process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effect of constant salinity (long term) has been assessed on embryos, larvae and juveniles (Pérez‐Robles et al, ; Pérez‐Robles, Re, Giffard‐Mena, & Díaz, ). These authors concluded that S. annulatus was a strong osmoregulator since oxygen consumption rate (OCR) and ammonium excretion rate (AER) rates were stable within salinity intervals from five to 40 psu in long‐term acclimation trials (21 days); O:N showed values from 50 to 60 indicating that S. annulatus used a mixture of proteins and lipids as source of energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation